The Effect of Employee Productivity on Public Services Through Improved Performance of the Human Resources Development Agency of North Sumatra Province - Nasution, Irma Safitri; Badaruddin; Rujiman (Journal of Environmental and Development Studies, 2023)
As an effort to build the quality of human resources, organizations need to carry out human resource development which is a process of increasing knowledge, skills and abilities in order to achieve national development goals which include planning, development and management. Through research on performance improvement at the North Sumatra Province human resource development agency, this study aims to analyze the effect of work productivity on public services. The population and sample in this study were prospective civil servants, Alumni of the Latsar state civil apparatus who had attended the Basic Training for prospective civil servants at the North Sumatra provincial human resource development agency totaling 120 (one hundred and twenty) people. The results of this study are: 1) There is a positive effect of work productivity on performance improvement; (2) there is no positive effect of work productivity on public services; (3) there is a positive effect of performance improvement on public services; (4) there is a positive direct effect of work productivity on public services through performance improvement; (5) there is an indirect effect of work productivity on public services through performance improvement.